The world as an asylum: between celebrities and medicine - Ruiz da Silva, Gustavo (Occursus - Revista de Filosofia, 2024)
What is the relationship between "mental health" enunciation’s growing process, currently explored by artists, like Lady Gaga and others, and the drugs aimed proliferation for medical-psychiatric patients’ correction in the post-asylums world? This problem can be studied by the methodological process developed by Michel Foucault (cf. 1979) in which some, like Deleuze, call his second phase: the studies on the power under the Nietzsche’s genealogical process. Knowing that, this essay intends to answer the above question and analyse the possible connection between heterogeneous lines, for example a type of medical discourse and pop culture in the emergence of something new.